2021
DOI: 10.31138/mjr.32.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Double Negative (DN) B cells: A connecting bridge between rheumatic diseases and COVID-19?

Abstract: Double Negative (DN) B cells constitute a B cell population that lacks expression of immunoglobulin D and CD27 memory marker. These cells expand in elderly healthy individuals, but also accumulate prematurely in autoimmune and infectious diseases. COVID-19 is a pandemic infectious disease caused by SARS-CoV-2, a coronavirus that was first observed in Wuhan, China in December 2019. In its more severe cases, COVID-19 causes severe pneumonia and acute respiratory syndrome with high morbidity and mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 70 publications
(158 reference statements)
0
12
0
Order By: Relevance
“…These reports suggest pathological implications of a range of autoantibodies in COVID-19 patients both at acute and post-infection manifestations. The mechanisms that give rise to autoantibodies during COVID-19 could be similar to the ones in malaria and SLE patients ( 61 ). Various studies have reported the expansion of ABCs and atypical B cells ( 20 , 62 ), a phenomenon that could be explained by the enhanced EF route of B cells reported in COVID-19 patients ( 63 ).…”
Section: Lessons From Malaria Applied To Covid-19 and Other Infectionsmentioning
confidence: 95%
“…These reports suggest pathological implications of a range of autoantibodies in COVID-19 patients both at acute and post-infection manifestations. The mechanisms that give rise to autoantibodies during COVID-19 could be similar to the ones in malaria and SLE patients ( 61 ). Various studies have reported the expansion of ABCs and atypical B cells ( 20 , 62 ), a phenomenon that could be explained by the enhanced EF route of B cells reported in COVID-19 patients ( 63 ).…”
Section: Lessons From Malaria Applied To Covid-19 and Other Infectionsmentioning
confidence: 95%
“…Interestingly, this raises the possibility that there are distinct T cell-independent and T cell-dependent pathways in B cells during COVID-19 disease, which is now suggested in other concurrent studies. IgE, therefore, can be produced by DN4 B cells, but serology from COVID-19 patients was not considered to be statistically relevant to this cellular subset [ 118 , 129 , 168 , 169 ]. IgE is known to cause mast cell degranulation through a higher affinity FcεRI receptor, and assay sensitivities require validation and development for this antibody normally seen in allergic responses with the IgG response predominant during infection.…”
Section: Innate Immune Systems and Sars-cov-2 Researchmentioning
confidence: 99%
“…Recently, these tools have become available in many centers worldwide due to the COVID-19 pandemic, which required these centers to provide dynamic protocols for RNA detection and/or sequencing [2]. These resources could be used to further significant progress in areas such as inflammatory rheumatic diseases [3]. In the few pages ahead, we highlight the possible application of these technologies in the rheumatology setting using potential RNA-based biomarkers with special emphasis on RA.…”
Section: Novel Gene Expression Analysis Technologies For Biomarkers D...mentioning
confidence: 99%